Reaksi Pasar Modal Terhadap Pengumuman Pembatalan Indonesia Sebagai Tuan Rumah Piala Dunia - Fitroh, Latifah; Mulyaningtyas (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2024)
The research aims to find out how the market reacted before and after it was announced that Indonesia would no longer host the World Cup. Market reactions are proxied through the use of abnormal return and trading volume activity. The research samples is LQ45 companies that listed on Indonesia Stock Exchange. Based on the research results, aberrant returns vary significantly before and after the announcement. However, when comparing trading volume before and after the announcement, the paired samples test shows no statistically significant differences. The results of this research indicate that the announcements before and after Indonesia withdrew as host of the World Cup did not led to significant changes in stock trading activity. However, this affect share price movements related to the above events.